2015
DOI: 10.1053/j.gastro.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A Hereditary Form of Small Intestinal Carcinoid Associated With a Germline Mutation in Inositol Polyphosphate Multikinase

Abstract: Background & Aims Small intestinal carcinoids are rare and difficult to diagnose and patients often present with advanced, incurable disease. Although the disease occurs sporadically, there have been reports of family clusters. Hereditary small intestinal carcinoid has not been recognized and genetic factors have not been identified. We performed a genetic analysis of families with small intestinal carcinoids to establish a hereditary basis and find genes that might cause this cancer. Methods We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 48 publications
1
67
0
Order By: Relevance
“…These syndromes include multiple endocrine neoplasia type 1 (MEN1) and von Hippel-Lindau syndrome (VHL), but also the less common neurofibromatosis type 1 (NF1) syndrome (Larsson et al 1988, Wallace et al 1990, Maher et al 1991. Familial small intestinal NET seem to have a wider spectrum of very rare mutations (Sei et al 2015, Dumanski et al 2017, even if no gene mutation has been mechanistically proven to directly cause this disease.…”
Section: Genetic Syndromesmentioning
confidence: 99%
See 2 more Smart Citations
“…These syndromes include multiple endocrine neoplasia type 1 (MEN1) and von Hippel-Lindau syndrome (VHL), but also the less common neurofibromatosis type 1 (NF1) syndrome (Larsson et al 1988, Wallace et al 1990, Maher et al 1991. Familial small intestinal NET seem to have a wider spectrum of very rare mutations (Sei et al 2015, Dumanski et al 2017, even if no gene mutation has been mechanistically proven to directly cause this disease.…”
Section: Genetic Syndromesmentioning
confidence: 99%
“…SI-NET tend to be multifocal in patients with IPMK mutations. A prospective study conducted on 33 families (Sei et al 2015), revealed a germline 4-bp deletion in the inositol polyphosphate multikinase (IPMK) gene on chromosome 10. This mutation was subsequently detected in all 11 affected individuals of this family but not in the other families, indicating that other genes are responsible for the onset of the disease.…”
Section: :9mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite substantial efforts no definitive genetic basis for this phenomenon has been described. A recent study used linkage analysis and exome sequencing that revealed IPMK germline mutations in a single family (135). Although experimental investigations seem to indicate a pathogenic effect of the IPMK mutation a validation effort that included 32 additional families did not reveal the presence of any additional mutations (135).…”
Section: Small Intestinal Netsmentioning
confidence: 99%
“…In this issue, investigators report on their strategy to identify kindreds with "familial carcinoid" and characterize these kindreds both clinically and genetically. 8 Sei et al 8 at the National Institutes of Health enrolled 33 kindreds with 2 first-degree relatives with small intestinal carcinoid tumors. Affected individuals were diagnosed with disease at an average age of 61 years, and 70% presented with stage IV disease.…”
mentioning
confidence: 99%